Psychological impact of COVID-19 outbreak among Jimma University Medical Centere visitors in Southwestern Ethiopia: a cross-sectional study - Yitayih, Yimenu (BMJ Open, 2021)
BACKGROUND: COVID-19 has posed several medical, psychosocial and economic impacts among the majority of the society. The ambiguity of its transmission, the intense desire of self-protection, family, and friends, the unknown impact of catching the disease itself, unstoppable spread, the panic and outright misinformation lead to acute stress reaction syndrome. However, reliable data related to this contagion lack the prevalence of acute stress reaction syndrome and associated factors among Jimma University Medical Centre hospital visitors in Southwestern Ethiopia. AIMS: The main objective of the study was to assess the prevalence and factors associated with acute stress reaction syndrome during the COVID-19 outbreak among Jimma University Medical Centre Hospital visitors, Ethiopia. METHODS: An interviewer-administered cross-sectional study was conducted among 247 visitors of the Jimma University Medical Centre in Ethiopia. The study was conducted within 2 weeks of the first COVID-19 cases detected on 13 March 2020 in Ethiopia. Data on demographic and socioeconomic status were collected during the interview using structured questionnaires. The psychological impact was assessed using the Impact of Event Scale-Revised, and symptoms of insomnia were measured using the Insomnia Severity Index. Social support was evaluated using Oslo three-item Social Support Scale. Logistic regression was employed to determine the associations between dependent and independent variables. Besides, psychosocial stress score was generated using principal component analysis. A paired permutation test was also performed to determine the variability of psychosocial stress between groups. RESULTS: The mean age of participants was 30.47 years, and 76.5% of the participants were male. Acute stress reaction syndrome was detected in 44.1% of hospital visitors. Of the participants, 38.5%, 17.4%, 8.5% and 35.6% had a minimal, mild, moderate and severe psychological impact, respectively. Factors positively associated with acute stress reaction syndrome were individuals who perceived that COVID-19 leads to stigma (adjusted OR (AOR): 3.24, 95% CI 1.11 to 9.45), mild insomnia (AOR: 14.74, 95% CI 6.14 to 35.40), moderate to severe insomnia (AOR: 35.1, 95% CI 10.76 to 114.66), low social support (AOR: 4.08, 95% CI 1.31 to 12.67) and governmental employees (AOR: 8.09, 95% CI 1.38 to 47.18). CONCLUSION: The study revealed the existence of a high prevalence of acute stress reaction syndrome during the COVID-19 outbreak among different groups of the community. Therefore, our results will contribute to the global awareness of the psychological impact of the COVID-19 outbreak.